(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Reducing energy consumption during pneumatic conveying cotton is a topical issue at the ginning plants. In this paper we consider the possibility of reducing energy costs by using smaller diameter pipes. It proposed a mathematical model and presents the analysis of energy consumption on parameters of the pneumatic conveyor and flow. Studies have established that the power spent on transporting the medium largely depends on the average flow rate, and then on the parameters (resistance of the inner surface, length and diameter) of the pipeline, and a significant part of the power is spent on air transportation. At the same time, the use of smaller diameter pipes at moderate flow rates reduces energy consumption and, consequently, reduces production costs at cotton gins.